Modeling dynamic responses of heterogeneous seabed with embedded pipeline through multiresolution random field and coupled hydromechanical simulations. (1st February 2019) - Lai, Zhengshou; Chen, Qiushi; Wang, Chaofeng; Zhou, Xianglian
Abstract: In this work, novel multiresolution random field models are integrated with coupled hydromechanical finite element simulations to model dynamic responses of heterogeneous seabed with embedded pipeline subjected to nonlinear wave-induced loadings. The heterogeneous properties of the seabed are characterized and modeled as spatially correlated random variables. A conditional sequential simulation technique is implemented and multiresolution random field realizations of heterogeneous properties are generated. The effects of spatially correlated seabed properties on the characteristic hydromechanical responses are analyzed in details through validated hydromechanical finite element simulations. Statistics and associated uncertainties of system response are obtained with recourse to Monte Carlo simulations. The relations between the inherent heterogeneities and uncertainties in the system responses are derived. Findings of this study are shown to have important implications for probabilistic engineering designs. Highlights: Novel multiscale random field are coupled with multiphysics finite element model. Simulate hydromechanical responses heterogeneous porous seabed – pipeline system. Effects of inherent heterogeneities of material properties are quantified with uncertainties. Implications on probabilistic engineering design are provided.